The distributional impact of carbon pricing and energy related taxation in Ireland - Cathal O'Donoghue; Herwig Immervoll; Zeynep Gizem Can; Jules Linden; Denisa M. Sologon (The Economic and Social Research Institute (ESRI), 2024)
In this paper we evaluate the distributional impact of carbon pricing in Ireland via a number of different measures, Excise Duties, Carbon Taxes and the EU Emissions Trading Scheme, utilising information contained in the OECD Effective Carbon Rate (ECR) database together with the PRICES model. Essential household energy consumption constitutes a significant portion of spending, particularly for lower-income households, indicating regressive expenditure patterns across income brackets. The immediate impact of carbon pricing on household budgets varies based on their reliance on various fuels for heating and transportation (direct impact), as well as the emissions associated with other goods and services (indirect impact). Carbon footprints vary widely among households, with higher-income ones generally emitting less than lower-income ones as a percentage of their income. Although carbon footprints primarily dictate the burdens of carbon pricing, other factors such as the uneven application of carbon pricing policies and disparities in emissions between industries and fuel types also influence the equation. Despite the necessity for substantial carbon price hikes to meet climate targets, the effects on household budgets during the 2012-2021 period were relatively modest. Carbon pricing reforms typically exhibited regressive trends, disproportionately affecting lower-income households relative to their earnings. We modelled also a number of different reforms utilising the revenue generated by the additional carbon revenues. The net impact in terms of winners and losers depended very significantly upon the both the nature of the expenditure and upon the share of revenue used.
Keywords: 330; Ireland; taxation; carbon pricing; energy